2007
DOI: 10.1016/j.jtcvs.2006.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Results of esophagectomy for esophageal cancer in elderly patients: Age has little influence on outcome and survival

Abstract: Increased experience and refinements in perioperative care explain the better results of esophagectomy in elderly patients in recent years. Short- and long-term outcomes after esophagectomy for carcinoma in patients older than 70 years are comparable with those of their younger counterparts. Advanced age per se thus should not be considered a contraindication to esophageal resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
122
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(134 citation statements)
references
References 15 publications
(16 reference statements)
12
122
0
Order By: Relevance
“…In several studies, the influence of old age was investigated [44][45][46][47][48][49][50][51][52][53][54][55][56] . In a minority of studies, older age was associated with an unfavourable postoperative outcome 44;49;52;53;55;56. The use of a risk score may be a quality indicator.…”
Section: Patient Selectionmentioning
confidence: 99%
“…In several studies, the influence of old age was investigated [44][45][46][47][48][49][50][51][52][53][54][55][56] . In a minority of studies, older age was associated with an unfavourable postoperative outcome 44;49;52;53;55;56. The use of a risk score may be a quality indicator.…”
Section: Patient Selectionmentioning
confidence: 99%
“…However, the most relevant treatment modalities in elderly patients with EC remain a subject of debate. It was reported that elderly patients are less likely to undergo surgery and chemotherapy, which is partially due to their comorbidities (3,4). Currently, CRT based on the 5-fluorouracil-cisplatin (5FU-CDDP) regimen is used for the treatment with curative intent of locally advanced or inoperable non-metastatic EC (5).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, advanced age alone may not exclude esophagectomy for patients with esophageal cancer. [18] Impaired preoperative pulmonary function has long been considered as an important tool for the evaluation of the risk of PCs after esophagectomy. [3,19,20] Avendano et al [19] and Shiozaki et al [20] reported that preoperative FEV 1 % less than 65% and 60% were associated with increased PCs after esophagectomy.…”
Section: Discussionmentioning
confidence: 99%